19F NMR Allows the Investigation of the Fate of Platinum(IV) Prodrugs in Physiological Conditions. (16th December 2021) - Yuan, Siming; Zhu, Yang; Dai, Yi; Wang, Yu; Jin, Duo; Liu, Manman; Tang, Liqin; Arnesano, Fabio; Natile, Giovanni; Liu, Yangzhong
Abstract: Pt IV prodrugs can overcome resistance and side effects of conventional Pt II anticancer therapies. By 19 F‐labeling of a Pt IV prodrug (Pt‐FBA, FBA=p‐fluorobenzoate), the activation under physiological conditions could be investigated. Unlike single‐electron reductants, multi‐electron agents can efficiently promote the two electrons reduction of Pt IV to Pt II . The activation of Pt‐FBA in cell lysate is highly dependent upon the type of cancer cells. When administered to E. coli, Pt‐FBA is reduced intracellularly and free FBA can shuttle out of the cell. The reduction rate greatly increases by inducing metallothionein overexpression and is lowered by addition of Zn II ions. When injected into mice, Pt‐FBA undergoes fast reduction in the bloodstream accompanied by metabolic degradation of FBA; nevertheless, unreduced Pt‐FBA can accumulate to detectable levels in liver and kidneys. The 19 F NMR approach has the advantage of avoiding the interference of all background signals. Abstract : By 19 F‐labeling of a Pt IV prodrug (Pt‐FBA, FBA= p ‐fluorobenzoate), the activation in vitro, in living cells and in mice could be investigated by NMR spectroscopy while avoiding the interference of all background signals and allowing the simultaneous detection of pre‐ and post‐activation species.